Cyclic axial compressive performance of hybrid double-skin tubular square columns - Wang, Dai; Yuan, Jian Song; Li, Yunchu; Fu, Quanchao; Zhang, Hengchang (Frontiers in Materials, 2023)
This paper presents an experimental study on the cyclic axial compressive behavior of FRP-concrete-steel hybrid double-skin tubular columns (DSTCs). The square column specimens were cast with an external FRP jackets, inner steel tube and concrete in between. The height of the columns was 500 mm and the side dimension was 150 mm. The effects of loading scheme, void ratio and diameter-thickness ratio on axial compression behavior were investigated. A total of eight columns were tested under monotonic and cyclic axial compression. The experimental results show that the effect of loading scheme on axial stress-strain envelope curve and the peak load were not significant, and the ultimate state of the square columns subjected to cyclic axial compression was very similar to that of specimens subjected to monotonic axial compression.Besides, compared with void ratio, the diameter-thickness ratio of the inner steel tube has significant influence on the peak load of the columns when subjected to cyclic axial compression.